Transformational Leadership Survey - Sunaengsih, Cucun; Komariah, Aan; Kurniady, Dedy Achmad; Suharto, Nugraha; Tamam, Badrud; Julia, Julia (Universitas Pendidikan Indonesia, 2021)
Several previous research have described transformational leadership as successful leadership that led higher education to implement changes for the better. However, a more comprehensive survey on the implementation of transformational leadership in higher education has not been conducted. This research aims at observing a transformational leadership style with the model 4I, namely idealized influence, intellectual stimulation, individual consideration, and inspirational motivation, which is applied to higher education comprehensively. A survey method with questionnaires taken from lecturers working at higher education in Indonesia was used in this research. The findings revealed that attention given to individuals and reducing penalty towards any mistakes by subordinates must be given more attention so that the application of complete combination between one dimension and other dimensions and each indicator of transformational leadership must be carried out. This research is expected to have implications for the effectiveness of higher education leadership, and be used as a reference by higher education leaders in choosing a leadership style.